Efficiency Analysis of Firm Financial Performance: Case Study of PT. Unilever Indonesia - Sumarti Sumarti (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the profitability ratios and companyliquidity ratios to assess the efficiency of company performance. This research isincluded in descriptive research, which is research that seeks to describe aphenomenon, event, event that is happening now. The reason this type of researchis used is because the researcher tries to describe the events and events that arethe center of attention without giving special treatment to those events. The studywas conducted at PT. Unilever Indonesia, is the largest manufacturing companyin Indonesia. The data analysis technique used in this study is quantitativedescriptive using financial ratio analysis. The results show financial performanceseen from the profitability ratio, overall the average is said to be efficient becauseof its magnitude above the industry average as a benchmark. Financialperformance can be seen from the liquidity ratio, overall the average ratio is saidto be liquid because the average is above the industry average as a benchmark.